2021
DOI: 10.1111/obr.13173
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder risk in adolescents with obesity

Abstract: Summary The intersection between adolescent obesity and eating disorder risk is one that requires urgent attention. This review aimed to synthesize the literature on the risk of clinical eating disorders in adolescents with obesity, discuss challenges with assessing risk, and examine implications for clinical practice and future research. Obesity and eating disorders can coexist resulting in exacerbated physical and psychological health issues. Recognized eating disorder risk factors, including body dissatisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 72 publications
0
64
1
Order By: Relevance
“…The current investigation adds to this literature by specifically examining the relationship between changes in the diet, rather than just participation in treatment, and eating pathology. Collectively, findings suggest that supervised dietary interventions within obesity treatment are not associated with increased eating pathology, which is in contrast to the observed relationships between unsupervised "dieting" and increased eating pathology among adolescents with obesity [25]. In this investigation, mean EDE-Q scores, both pre-and post-treatment, are well below the clinical cut-off score of >4 [26].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The current investigation adds to this literature by specifically examining the relationship between changes in the diet, rather than just participation in treatment, and eating pathology. Collectively, findings suggest that supervised dietary interventions within obesity treatment are not associated with increased eating pathology, which is in contrast to the observed relationships between unsupervised "dieting" and increased eating pathology among adolescents with obesity [25]. In this investigation, mean EDE-Q scores, both pre-and post-treatment, are well below the clinical cut-off score of >4 [26].…”
Section: Discussioncontrasting
confidence: 79%
“…While the changes in dietary intake reflected the treatment goals, it is important to note that there was a large amount of variability in the response. This amount of variability to intervention response has been one of the major reasons why the focus on "precision medicine" has developed [25]. A component of this is precision nutrition, which is focused on identifying moderators to dietary treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important given the concerns that TLE may lead to unhealthy eating behaviors and attitudes. Disordered eating behaviors are prevalent among adolescents with obesity; however, many studies have suggested that monitored intervention programs implemented by trained professionals may decrease eating behavior symptomatology [82][83][84]. The potential for unhealthy eating should be continuously monitored in future studies [73,83,85].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of obesity and ED treatment interventions in adolescents [ 89 , 90 ] have concluded that structured obesity treatment programs for adolescents reduce eating disorder prevalence, risk, and symptoms, [ 90 ] as well as reducing shape and weight concerns [ 91 ]. These findings also suggest that while these “supervised” interventions are not associated with increased eating pathology, unsupervised “dieting”, as a self-reported method to lose weight, e.g., fasting, skipping meals, and diet pill use, has been associated with increased eating pathology among adolescents [ 92 ]. Additionally, not all individuals at increased risk maybe adequately be identified in aggregate data [ 93 ].…”
Section: Implications Of Findings Past and Presentmentioning
confidence: 99%